ANALYSIS OF SHEARER VIBRATION CHARACTERISTICS UNDER DIFFERENT LIFT ANGLE - MAO Jun; YANG XinWei; SONG QiuShuang (Jixie qiangdu)
According to shearer vibration problems in the practical work,using multi-body dynamics theory,considering shearer support characteristics of guide boots and flat boots,and the stiffness of rocker arm and adjustment height oil vat,6 degrees of freedom dynamic model in the vertical direction of shearer was established.The vertical direction of shearer drum load was used as an external excitation,and the effect of different lift angle on vertical direction vibration characteristics of shearer were solved by using numerical analysis method.The results show that the lift angle has great influence on vibration displacement of drum and ranging arm when the range is 17° 37°,and the displacement range is 21.5521 15.424 mm,9.4005 ~3.306 4 mm.Because of the low frequency vibration of shearer under actual operating conditions,the vibration acceleration under different lift angle is insensitive.